Edaphic fauna in built areas after open air coal mining Fauna edáfica em áreas reconstruídas após mineração de carvão a céu aberto - Segat J.C.* (2021)
© 2021 University Center of Maringa. All rights reserved.Open air coal mining causes environmental impacts due to the inadequate deposits of wastes and to contamination by pyrite oxidation. Current paper evaluates edaphic fauna under different system of soil reconstitution and management after open air coal mining. The paper's hypothesis is that reconstitution with limestone and organic fertilization are rather more effective in rehabilitation. Assay's design comprised randomized blocks with three replications: control without reconstitution; reconstitution + limestone; reconstitution + limestone + aviary bed; reconstitution + limestone + cattle; reconstituted area; and natural field. Fauna was collected every 60 days, between April and October. Data were submitted to ANOVA and compared by LSD test (p≤ 0.05). Indexes were clustered and submitted to correspondence analysis. Results show that, during implementation, the effects of liming and organic fertilization caused cattle improve indexes, especially in terms of fauna diversity.